2022
DOI: 10.1177/17455057221125091
|View full text |Cite
|
Sign up to set email alerts
|

Non-utilization of postnatal care and its associated factors among women who gave birth in rural districts of Northern Ethiopia: A community-based mixed-method study

Abstract: Objectives: This study assessed the non-utilization of PNC services, identified factors associated with PNC non-utilization, and explored barriers to PNC utilization in the rural community. Method: A community-based mixed-cross-sectional study was conducted from 20 March to 20 April 2020 among 521 women who gave birth in the last 12 months prior to this survey. A multistage sampling and face-to-face interview techniques were used for the quantitative data collection, and a purposive sampling technique was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Existing evidence shows that Antenatal Care (ANC) is an appropriate gateway for the full package of maternal health care services [ 6 ] and those with good adherence to ANC visits are more likely to stick to the remaining services in the continuum of maternal health care services compared to those with poor compliance [ 7 , 8 ]. On the other hand, ANC visits should be accompanied by provision and utilization of the essential components which are said to be the building blocks of the care in ensuring its quality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence shows that Antenatal Care (ANC) is an appropriate gateway for the full package of maternal health care services [ 6 ] and those with good adherence to ANC visits are more likely to stick to the remaining services in the continuum of maternal health care services compared to those with poor compliance [ 7 , 8 ]. On the other hand, ANC visits should be accompanied by provision and utilization of the essential components which are said to be the building blocks of the care in ensuring its quality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four previous studies have identified the factors affecting utilization or non-utilization of maternal healthcare services and these studies were conducted in China [ 19 ], Ethiopia [ 20 , 21 ], and India [ 22 ]. Factors associated with the use of maternal health services included travel distance to the hospital and women's perception, choice, autonomy, and characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…source of referral, pain and disability) [ 23 ], it remains unknown whether disparities exist in terms of factors associated with physical therapy utilization versus overall medical utilization in pregnant and postpartum women due to the lack of direct access to physical therapy in some countries or locations (i.e. Taiwan) [ 24 ] and socio-cultural differences among countries [ 21 ]. While evidence supports physical therapy as a safe and effective treatment option for women at various life stage [ 25 ], to date, no studies have compared the characteristics of women who utilized and did not utilize physical therapy during pregnancy and/or after childbirth in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Postnatal care obstacles and other factors have been found in prior work. Findings from studies conducted in Jabitena district, Amhara regional state, Northwest Ethiopia, Northern Ethiopia, and Wolkite, Ethiopia, as well as rural areas of Northern Ethiopia, Tigray, Ethiopia, Debre Tabor town, Northern Ethiopia, Hawassa Zuria, Northern Ethiopia at Adigirat town, Addis Ababa, in Sodo Zuria and Shebe Sombo Woreda, Jimma, revealed that the prevalence of postnatal service utilization ranges from 20.2% to 77.7% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The number of children ever delivered, the mother's level of literacy, and radio listening frequencies were determined to be the drivers of PNC use in a study conducted in parts of Ethiopia. Other factors such as more than four pregnancies, wanted pregnancy, spontaneous vertex delivery, husband with secondary education, delivery with cesarean section, secondary education or above for the mother, a monthly household income of more than 1,500 ETB, planned and supported prior pregnancy, institutional delivery of last pregnancy, accessing health care, having a positive attitude towards the use of postnatal services, and having a living child born from the previous pregnancy show significant associations with postnatal service utilization (13,14,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%